Construction of a Five-Super-Enhancer-Associated-Genes Prognostic Model for Osteosarcoma Patients - Ouyang, Zhanbo; Li, Guohua; Zhu, Haihong; Wang, Jiaojiao; Qi, Tingting; Qu, Qiang; Tu, Chao; Qu, Jian; Lu, Qiong (Frontiers in Cell and Developmental Biology, 2020)
Osteosarcoma is a malignant tumor most commonly arising in children and adolescents, and associated with poor prognosis. In recent years, some prognostic models have been constructed to assist clinicians in the treatment of osteosarcoma. However, the prognosis and treatment of patients with osteosarcoma remain unsatisfactory. Notably, super-enhancer (SE)-associated genes strongly promote the progression of osteosarcoma. In the present study, we constructed a novel effective prognostic model using SE-associated genes from osteosarcoma. Five SE-associated genes were initially screened through the least absolute shrinkage and selection operator penalized Cox regression, as well as univariate and multivariate Cox regression analyses. Meanwhile, a risk score model was constructed using the expression of these five genes. The excellent performance of the five SE-associated gene-based prognostic model was determined via time-dependent receiver operating characteristic curves and Kaplan–Meier curves. Inferior outcome of overall survival was predicted in the high-risk group. A nomogram based on the polygenic risk score model was further established to validate the performance of the prognostic model. It showed that our prognostic model performed outstandingly in predicting 1-, 3-, and 5-year overall survival of patients with osteosarcoma. Meanwhile, these five genes also belonged to the hub genes-associated with survival and necrosis of osteosarcoma according to the result of weighted gene co-expression network analysis based on the dataset of GSE39058. Therefore, we believe that the five-SE-associated-gene-based prognostic model established in this study can accurately predict the prognosis of patients with osteosarcoma, and effectively assist clinicians in treating osteosarcoma in the future.